Investigating the potential for using gamification to empower knowledge workers. (1st December 2020) - Spanellis, Agnessa; Dӧrfler, Viktor; MacBryde, Jillian
Highlights: Gamification can empower and cater to a specific type of knowledge workers. Transaction model of knowledge work becomes more collaborative with gamification. Enacted information model of knowledge work becomes more creative with gamification. Gamification can provide more autonomy and flexibility to knowledge workers. Gamification can help to reveal new knowledge worker roles. Abstract: The increasingly popular trend of gamification has proved powerful in many areas, such as education and marketing, and has started making its way to the corporate environment. This exploratory study is focused on a particular part of corporate applications – using gamification to empower knowledge workers and to help them to interact with each other. Based on a review of the extant literature and an exploratory case study, we conceptualise different ways in which gamification supports knowledge workers and influences the dynamics of their interactions. The case study we present is that of online retailer Zappos who have been pioneers in this field. This paper is intended as the beginning of a journey towards utilising gamification in various aspects of knowledge work. Through studying the Zappos case, we draw out key learning points that can be used by other organisations in their journey to use gamification to empower knowledge workers. The paper also identifies areas for further research relevant to expert and intelligent systems, including the potential for synergies between gamification and intelligent systems, and the use of gamification in intelligent systems implementation.